Comprehensive Analysis of the Immune Cell Infiltration Landscape and Immune-Related Methylation in Retinoblastoma - Mao, Peiyao; Shen, Yinchen; Xu, Xun; Zhong, Jiawei (Frontiers in Genetics, 2022)
Retinoblastoma is a common pediatric intraocular cancer, originating from cone precursors. Development of immunotherapies can eradicate the tumor without vision loss, which would largely improve the quality of life of patients with retinoblastoma. Investigation of tumor immune microenvironment provides knowledge for novel immunotherapies in cancer. However, immune cell infiltrative landscape of retinoblastoma is unknown. Here we compared the relative expression of immune gene signatures among 59 patients with retinoblastoma. Patients were divided into two subgroups according to the 28 types of immune cell infiltration (ICI) scores. We found that a subgroup with high ICI scores had increased expression levels of late cone markers, while other subgroup exhibited higher tumor size and metastasis propensity. Furthermore, hypermethylated genes in high-ICI subgroup were associated with immune regulation in tumor microenvironment, suggesting that DNA methylation may play a vital regulatory role in retinoblastoma immunity. Our study provides a comprehensive framework for systemic analysis of the influences of epigenetic events on tumor immune microenvironment. We anticipate our assay can not only provide insights into tumor immune regulation, but also open up the perspectives for identification of novel immunotherapy targets for retinoblastoma.